'Is the Picture Worth a Thousand Words?': The Interpersonal Meanings of a Dialogue in an EFL Textbook - Sugianto, Ahmad; Prasetyo, Ilham Agung; Asti, Widy (Journal of Languages and Language Teaching, 2022)
This study was aimed at scrutinising a multimodal text embedded in a dialogue of an EFL textbook. To this end, Systemic Functional Multimodal Discourse Analysis (SF-MDA) focused on interpersonal meanings consulting grammar of visual design and intersemiotic complementarity drawing on systemic functional linguistics were employed to analyse the artefact, a dialogue within a part named 'communication' taken from an EFL textbook for a primary school level. The findings revealed that declarative clause and modalisation (epistemic modality) of probability was found to be the most common system used in the verbal text. Meanwhile, high modality and validity were found in the visual image indicated by the realisations and representations of detailed abstraction and full-colour saturation. Finally, the study draws a conclusion that there is a cohesive interaction to a certain extent between the verbal text and the visual image represented in the multimodal dialogue.